Effect of load models on Battery-Switching Station allocation in distribution network - Jamian, J.J.; Mustafa, M.W.; Muda, Z.; Mokhlis, Hazlie; Aman, M.M. (2012)
Battery-Switching Station (BSS) is one of the most important components in the growth of electrical vehicle (EV) market. In the distribution network point of view, these BSS units are a new type of load in the distribution system for charging the EV. The charging process consume real power, thus the nature of BSS load is purely resistive. Without proper allocation of BSS units, it might cause the power losses in the distribution system increase dramatically. In the present study, BSS units are located optimally utilizing Artificial Bee Colony (ABC) algorithm. The 33-bus distribution system with three distributed generators (DG) units using different load types is used as a test system. The result shows that the optimal location of BSS units does not affect the load types but has an impact to the power losses and voltage profile value.